Exploring the Legacy of Halldór Laxness: Contemporary English-Language Perspectives on Iceland's Greatest Twentieth-Century Writer - Brandsma, Elliott J., 1990- (2016)
In 1955, the Swedish Academy awarded the Nobel Prize in Literature to Halldór Kiljan Laxness, who was at the time a controversial yet highly-venerated Icelandic novelist. Although his most notable work, Independent People, appeared in English translation as a popular Book-of-the-Month-Club selection just prior to his Nobel win, Laxness largely faded from public consciousness in the English-speaking world for decades thereafter, falling out of U.S. publishersʼ favor due to his strident left-wing and anti-American views, among other reasons. During the late 1990s, American writer, professor, and Laxness enthusiast Brad Leithauser lobbied and convinced Vintage International to reprint Laxnessʼ works in English. However, this prolonged absence has, undoubtedly, taken its toll on the celebrated authorʼs legacy in the U.S, diminishing his readership, thereby complicating further literary research. Although fresh English translations of several of Laxnessʼ major works have recently emerged, a dearth of rich, contemporary critical perspective about them persists within American academic circles. Because Laxness remains a towering, influential literary figure in Iceland and across Scandinavia, his works merit greater critical attention in English, and his myriad contributions to world literature certainly warrant reexamination. Using personal anecdotes, interviews with writers and public figures, and archival research, this thesis seeks to explore and investigate the complex causes behind Laxnessʼ decades-long disappearance from the U.S. book market, as well as prompt a renewed conversation, in English, about the relevance of Laxnessʼ art in the twenty-first century.